Basalt petrogenesis beneath slow- and ultraslow-spreading Arctic mid-ocean ridges - Elkins, Lynne J (Massachusetts Institute of Technology, 2009)
Thesis (Ph. D.)--Joint Program in Marine Geology and Geophysics (Massachusetts Institute of Technology, Dept. of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), 2009. Includes bibliographical references. To explore the ability of melting mafic lithologies to produce alkaline ocean-island basalts (OIB), an experimental study was carried out measuring clinopyroxene (Cpx)melt and garnet (Gt)-melt partition coefficients during silica-poor garnet pyroxenite melting for a suite of trace elements, including U and Th, at 2.5GPa and 1420-1450°C. Partition coefficients range from 0.0083+0.0006 to 0.020+0.002 for Th and 0.0094+0.0006 to 0.024+0.002 for U in Cpx, and are 0.0032+0.0004 for Th and 0.013+0.002 for U in Gt. Forward-melting calculations using these experimental results to model time-dependent uranium-series isotopes do not support the presence of a fixed quantity of garnet pyroxenite in the source of OIB. To use U-series isotopes to further constrain mantle heterogeneity and the timing and nature of melting and melt transport processes, U-Th-Pa-Ra disequilibria, radiogenic isotopes, and trace-element compositions were measured for the slow-spreading Arctic mid-ocean ridges (MOR). A focused case study of 33 young (<10ka) MOR basalts (MORB) from the shallow endmember of the global ridge system, the Kolbeinsey Ridge (67°05'-70°26'N) found that unaltered Kolbeinsey MORB have universally high (230Th/238U) (1.165-1.296) and relatively uniform (230Th/232Th) (1.196-1.324), ENd (8.4310.49), 87Sr/86Sr (0.70274-0.70301), EHf(16.59-19.56), and Pb isotopes (e.g. 208Pb/206Pb 2.043-2.095). This suggests a homogeneous mantle source and a long peridotite melting column produces the thick Kolbeinsey crust. Trace element ratios suggest a young, depleted mantle source. Data from the slow- to ultraslow Mohns and Knipovich Ridges north of Kolbeinsey form a sloped array, and (230Th/232Th) correlates systematically with radiogenic isotopic variations. (cont.) These data are readily ...